Psychiatric outcomes observed in patients living with HIV using six common core antiretrovirals in the Observational Pharmaco-Epidemiology Research and Analysis database. (December 2018) - Hsu, Ricky; Fusco, Jennifer; Henegar, Cassidy; Mounzer, Karam; Wohlfeiler, Michael; Vannappagari, Vani; Aboud, Michael; Curtis, Lloyd; Fusco, Gregory
Background: Psychiatric outcomes are common among people living with HIV and may be associated with specific antiretroviral use. We evaluated the occurrence of psychiatric outcomes in patients taking dolutegravir (DTG)-containing regimens compared with five other core agents. Methods: Patients in the OPERA database prescribed regimens based on DTG, efavirenz (EFV), raltegravir (RAL), darunavir (DRV), rilpivirine (RPV), or elvitegravir (EVG) for the first time between 1 January 2013 and 31 December 2015 were analyzed. Psychiatric outcomes included diagnoses of anxiety, depression, insomnia, or suicidality during core agent exposure. Multivariable Cox analysis models were used to assess time to psychiatric outcomes between core agents stratified by psychiatric history, with DTG as the referent. Results: A total of 13, 261 patients initiated a regimen of interest (DTG: 2783; RAL: 979; EVG: 3895, EFV: 1746, RPV: 1921, DRV: 1937). Psychiatric history was common, with varied prevalence across groups (DTG 38%, EFV 24%, RAL 40%, DRV 34%, RPV 29%, EVG 31%). Among patients without a psychiatric history, the likelihood of a psychiatric outcome during follow up did not differ between DTG and the other core agents. Among patients with a psychiatric history, risk during follow up for patients taking DTG was equivalent ( versus RPV), marginally reduced ( versus RAL and EFV), or reduced ( versus EVG and DRV). Conclusions: In a large cohort of HIV+ patients in care, patients with a psychiatric history appeared channeled towards drugs with known favorable psychiatric safety profiles, including DTG. Despite this, DTG exposure was not associated with an increased risk of psychiatric outcomes during follow up in patients with or without a psychiatric history.